Pengaruh Motivasi dan Kedisiplinan Kerja terhadap Kinerja Karyawan pada BKKBN Unit Kerja Pusat Penelitian dan Pengembangan Keluarga Berencana dan Keluarga Sejahtera (PUSNA) - Miftakhul Qirom (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study aims to determine: (1) the influence of motivation on employee performance, (2) the influence of work discipline on employee performance, (3) the influence of motivation and work discipline on employee performance at the National Population and Family Planning Agency (BKKBN) Family Planning and Family Welfare Research and Development Center (PUSNA) Work Unit. This study was conducted at the National Population and Family Planning Agency (BKKBN) Family Planning and Family Welfare Research and Development Center (Pusna) in the field of population control and family planning with motivation and work discipline as independent variables and employee performance as the dependent variable. This study used a sample of 44 people determined by the Slovin sample. Data collection techniques through observation and questionnaires. Instrument testing uses validity and reliability tests, while data analysis techniques used are classical assumption tests and multiple linear regression using SPSS 25. The results of the study indicate that motivation and work discipline variables simultaneously have a positive and significant effect on employee performance. While partial testing shows that motivation and work discipline have a significant effect on employee performance. Furthermore, motivation is the dominant factor that influences employee performance.